Sikap Kerja Lebih Ergonomis Menurunkan Gaya Kompresi Tulang Belakang dan Keluhan Muskuloskeletal serta Meningkatkan Produktivitas - Cintya Dewi, Komang Ayu; Tirtayasa, Ketut; Adiputra, Luh Made Indah Sri Handari (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2019)
The role of construction workers is very important in the process of building or renovating a house. When construction workers lift sand using a hand cart, workers perform a bent stance with a lifting load that is high enough so the spinal force compression reaches 7449 N (L5/S1) which is included in the danger category because it exceeds the maximum premissible limit by NIOSH. The work posture also triggers musculoskeletal complaints especially in the back muscles. The purpose of this study was to find out the effect of work posture that more ergonomically on spinal force compression, musculoskeletal complaints and work productivity. The population was all construction workers in Denpasar with a sample of 8 people. The study was conducted in April-May 2019 in one of the houses that were build in the city of Denpasar. Measurement of spinal force compression variables using biomechanical analysis through manual count and using 3D SSPP software and musculoskeletal complaints using Nordic Body Map. The results showed work posture that more ergonomically in construction workers in Denpasar could reduce respectively L5/S1 compression force 67.25%, decrease in L4/L5 compression force 64.34%, decrease in musculoskeletal complaints 4.92% (p<0.05), and increase work productivity of 5.97% (p<0.05). It was concluded were work posture that more ergonomically can reduce spinal force compression, musculoskeletal complaints and increase work productivity. Recommended for all construction workers to apply ergonomically work posture to avoid work-related illnesses.